A comparative study of recent lubri-coolant strategies for turning of Ni-based superalloy. (December 2017) - Behera, Bikash Chandra; Alemayehu, Habtamu; Ghosh, Sudarsan; Rao, P. Venkateswara
Abstract: This paper deals with a comparative study of High-pressure jet, cryogenic, minimum quantity lubrication and minimum quantity lubrication with nanofluid cutting environments during machining of Inconel 718 superalloy. Inconel 718 has been chosen for this study because of its wide applications in spacecraft, defense, and energy sectors. The important machining process parameters such as speed, feed, and rake angle have been chosen and their different levels have been used based on tool-work combination. Cutting force, flank wear and surface finish have been analyzed. Additionally, surface defects, surface topography, residual stress on the machined surface and chip morphology have been studied. The results show that the cryogenic environment results in better surface integrity and reduced tool wear during machining of Inconel 718.